Suggestion of Two Authenticated Encryption Algorithms: Lightweight Chach20-Photon and Blowfish-Sha512 to Secure IoT-Edge-Cloud Networks - Hasoun, Rajaa K.; Al-Adhami, Ayad; Jabber, Sanaa A.; Hashem, Soukaena H. (Iraqi Journal of Science, 2026)
Edge networks are decentralized networks that allocate computing resources at the network’s periphery. It reduces the need for data centres and cloud computing by bringing processing power and data storage closer to devices. This architecture improves reaction times and performance, especially for latency-sensitive and data-intensive applications. Edge networks, like any technology, have drawbacks; security is one of these. Protecting the data traveling over IoT Edge-Cloud nodes is critical. Authenticated Encryption (AE) algorithms are the best solution to provide data secrecy, integrity, and authenticity for data over these multi-node networks. This study seeks to secure the connection among IoT devices, edge servers, and cloud data centres, for IoT/Edge network proposed, lightweight chach20-photon AE is recommended, where the recommendation for the Edge/cloud network is the proposed Blowfish-Sha512 AE. From experimental results and comparisons, ChaCha20-Photon provides (50 Mbps) throughput, (15 Mbps) MAC generation, (2 ms) latency, (100 µJ) energy consumption, and high security, as compared with strong ChaCha20-Poly1305, which is commonly used in high-performance and strong security protocols such as Transport Layer Security (TLS), Secure Shell (SSH), and secure messaging apps. Blowfish-SHA-512 provides (20mbps) throughput, (19mbps) MAC Generation, (5 ms) latency, (200 µJ) energy consumption, and high security in comparison with strong Advanced Encryption Standard- Galois/Counter Mode (AES-GCM(, which is extensively used in various security protocols, including Transport Layer Security (TLS), Internet Protocol Security (IPsec), and virtual private networks (VPNs).